2010
DOI: 10.17705/1jais.00225
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration into the Process of Requirements Elicitation: A Grounded Approach

Abstract: Requirements elicitation (RE) is a critical phase in information systems development (ISD), having significant impacts on software quality and costs. While it has remained a key topic of interest for IS researchers, a review of the existing literature suggests that there are very few studies examining how the social process associated with RE unfolds. Prior literature acknowledges that this process involves collaboration between RE participants (e.g., user-reps and systems analysts) where knowledge regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 88 publications
(107 reference statements)
0
71
0
3
Order By: Relevance
“…According to Chakraborty, Sarker, and Sarker (2010), requirements can be elicited from the clients, business users, or process owners. According to Schlegel (2011, p. 5), "this entails being able to find the story buried in every process and communicating it to a wider audience in either a written or oral context."…”
Section: Business Requirement Elicitation Competencymentioning
confidence: 99%
“…According to Chakraborty, Sarker, and Sarker (2010), requirements can be elicited from the clients, business users, or process owners. According to Schlegel (2011, p. 5), "this entails being able to find the story buried in every process and communicating it to a wider audience in either a written or oral context."…”
Section: Business Requirement Elicitation Competencymentioning
confidence: 99%
“…Similar trends of research shift existed already in the broad field of conceptual modeling (e.g., Hoppenbrouwers et al 2005) and the even more general area of system analysis and development (e.g., Chakraborty et al 2010;Nunamaker and Chen 1990). The underlying assumption in all of these studies is that the quality of the product depends on the quality of the process that creates the product, at least to some extent.…”
Section: Introductionmentioning
confidence: 71%
“…The modeler forms a mental representation of the process based on direct observation and/or various descriptions of the real or intended process such as interview transcripts, whiteboard notes and requirements documents (Chakraborty et al 2010). It should also be noted that mental models are rarely stable, they keep evolving as more information is processed (Rogers and Rutherford 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These literatures covered various techniques to improve RE effectiveness Table 2. In spite of these fruitful studies, many limitations have been identified by scholars (Chakraborty et al, 2010).…”
Section: Isd Knowledge Sharingmentioning
confidence: 99%